Hetaerina calverti (Odonata: Zygoptera: Calopterygidae) sp. nov., a new cryptic species of the American Rubyspot complex - Vega-Sánchez, Yesenia Margarita; Mendoza-Cuenca, Luis Felipe; González-Rodríguez, Antonio (Zootaxa, 2020)
Hetaerina americana Fabricius, 1798 has a long and irresolute taxonomic history. Several synonyms have been suggested (H. californica Hagen in Selys-Longchamps, 1859, H. basalis Hagen in Selys-Longchamps, 1859, H. texana Walsh, 1863, H. scelerata Walsh, 1863, etc.), related to the variation in the size of the wing spots as well as to the morphology of the male cerci. However, Calvert (1901) suggested that H. americana represents one variable species. Nevertheless, Vega-Sánchez et al. (2019) through a genetic and morphological analysis presented evidence to propose that H. americana represents a species complex. In the present work, we describe a new species that belongs to this complex: H. calverti sp. nov. The morphological characteristics by which males and females of H. calverti differ from H. americana are highlighted. The most important character for the differentiation of males is the shape of the cerci and the size of the individuals (when the two species are in sympatry). In females, the main differences are in the shape of the intersternites and the medio-dorsal carina of the last segment of the abdomen. Some generalities about the biology of the species are presented, including geographical distribution patterns and genetic divergence data. [urn:lsid:zoobank.org:act:F5C329AE-7A00-4979-8A0D-A13D869E54B1]